Makkovik, Landungsbrücke mit Bruder Jannasch von hinten : [ca. 1900] - Hettasch, Paul, 1873-1949. (2001)
Black and white photograph of the wharf at Makkovik. Missionary Hermann Jannasch is pictured back on. Black and white photograph of the wharf at Makkovik. Missionary Hermann Jannasch is pictured back on.